Transcranial direct current stimulation over right dorsolateral prefrontal cortex enhances error awareness in older age - Robertson, Ian; O'Connell, Redmond (My University, 2014)
The ability to detect errors during cognitive performance is compromised in older age and in a range of clinical populations. This study was designed to assess the effects of transcranial direct current stimulation (tDCS) on error awareness in healthy older human adults. tDCS was applied over DLPFC while subjects performed a computerized test of error awareness. The influence of current polarity (anodal vs cathodal) and electrode location (left vs right hemisphere) was tested in a series of separate single-blind, Sham-controlled crossover trials, each including 24 healthy older adults (age 65-86 years). Anodal tDCS over right DLPFC was associated with a significant increase in the proportion of performance errors that were consciously detected, and this result was recapitulated in a separate replication experiment. No such improvements were observed when the homologous contralateral area was stimulated. The present study provides novel evidence for a causal role of right DLPFC regions in subserving error awareness and marks an important step toward developing tDCS as a tool for remediating the performance-monitoring deficits that afflict a broad range of populations.
PUBLISHED
Keywords: tDCS; prefrontal cortex; performance monitoring; error awareness;; cognitive aging; Ageing; Neuroscience